Resin composition

The resin composition addresses the issue of low glass transition temperature and flowability in current resin compositions by incorporating specific resins and crosslinking agents, ensuring low dielectric constant and improved processability for high-frequency and high-speed transmission applications.

JP2024180228AInactive Publication Date: 2024-12-26NANYA PLASTICS CORP

Patent Information

Application Number
JP2023149751
Authority / Receiving Office
JP · JP
Patent Type
Applications
Current Assignee / Owner
Priority Date
2023-06-14
Filing Date
2023-09-15
Publication Date
2024-12-26
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

Current resin compositions for copper-clad laminates have low dielectric constants but suffer from reduced glass transition temperature and flowability, making them unsuitable for high-frequency and high-speed transmission applications.

Method used

A resin composition comprising a first resin polymerized from a monomer mixture of styrene, divinylbenzene, and ethylene, a bismaleimide-modified polyphenylene ether resin, a divinylbenzene-based crosslinking agent, spherical silica, and a siloxane coupling agent, which maintains low dielectric constant while increasing glass transition temperature and flowability.

Benefits of technology

The resin composition achieves low dielectric constant electrical specifications with improved glass transition temperature and flowability, enhancing processability for high-frequency and high-speed transmission applications.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 2024180228000001
    Figure 2024180228000001
  • Figure 2024180228000002
    Figure 2024180228000002
  • Figure 2024180228000003
    Figure 2024180228000003
Patent Text Reader

Abstract

To provide a resin composition that effectively increases glass transition temperature while maintaining electrical specifications with low dielectric constants.SOLUTION: A resin composition includes a first resin polymerized by a monomer mixture including styrene, divinylbenzene, and ethylene, a second resin including a bismaleimide-modified polyphenylene ether resin, a divinylbenzene crosslinking agent, a halogen-free flame retardant, a spherical silica, and a siloxane coupling agent.SELECTED DRAWING: None
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present invention relates to a resin, and in particular to a low dielectric constant resin composition. [Background technology]

[0002] In recent years, with the development of 5G communications, copper-clad laminate materials with the aim of achieving low dielectric constant (low-k) have been developed. The dielectric constant (Dk) of current boards is around 3.2 to 5.0, which is not suitable for future high frequency and high speed transmission applications. In the current low dielectric constant method, a certain percentage of a new low dielectric constant resin (polyDVB, hereinafter referred to as the first resin) can be added to reduce the electrical properties until the dielectric loss tangent (Df) is less than 0.0015. However, while achieving low electrical specifications, the glass transition temperature (Tg) may be lowered or the flowability may be reduced, resulting in a decrease in overall processability. Summary of the Invention [Problem to be solved by the invention]

[0003] Therefore, in order to achieve good processability of the resin composition, development of a resin composition that can increase the glass transition temperature and / or improve the flowability while maintaining the electrical specification of low dielectric constant is a challenge that the industry is trying to achieve. [Means for solving the problem]

[0004] The present invention provides a resin composition that has the effect of increasing the glass transition temperature while maintaining the electrical specification of a low dielectric constant.

[0005] The resin composition of the present invention includes a resin base material, a halogen-free flame retardant, spherical silica, and a siloxane coupling agent. The resin base material includes a first resin, a second resin, and a divinylbenzene-based crosslinking agent. The first resin is polymerized with a monomer mixture including styrene, divinylbenzene, and ethylene. The second resin includes a bismaleimide-modified polyphenylene ether resin.

[0006] In one embodiment of the present invention, the content of the first resin is 30 to 60 parts by weight, the content of the second resin is 20 to 40 parts by weight, and the content of the divinylbenzene-based crosslinking agent is 10 to 30 parts by weight, relative to 100 parts by weight of the resin substrate.

[0007] In one embodiment of the present invention, the amount of the halogen-free flame retardant added is 20 phr to 50 phr based on 100 parts by weight of the resin substrate.

[0008] In one embodiment of the present invention, the amount of spherical silica added is 20 parts by weight to 50 parts by weight based on 100 parts by weight in total of the resin base and the non-halogen flame retardant.

[0009] In one embodiment of the present invention, the molar ratio of styrene:divinylbenzene:ethylene in the first monomer mixture is from 1:1:1 to 2:2:1.

[0010] In one embodiment of the present invention, the first resin has a number average molecular weight of 4,500-6,500.

[0011] In one embodiment of the present invention, the resin substrate further comprises an SBS resin polymerized from a second monomer mixture comprising styrene, 1,2-butadiene, and 1,4-butadiene.

[0012] In one embodiment of the present invention, the molar ratio of styrene:1,2-butadiene:1,4-butadiene in the second monomer mixture is from 1:6:4 to 4:9:3.

[0013] In one embodiment of the present invention, the content of the SBS resin is 0 to 30 parts by weight based on 100 parts by weight of the resin substrate.

[0014] In one embodiment of the present invention, the weight average molecular weight of the SBS resin is 3,500-5,500.

[0015] In one embodiment of the present invention, the spherical silica is surface-modified with acrylic or vinyl and has an average particle size D50 of 2.0 μm to 3.0 μm.

[0016] In one embodiment of the present invention, the electrical specifications of the resin composition include a dielectric constant of 3.0 to 3.1 and a dielectric loss tangent of less than 0.0015, and the heat resistance specifications of the resin composition include a glass transition temperature of more than 210°C. Effect of the Invention

[0017] Based on the above, the resin composition of the present invention can be made to have low dielectric constant electrical specifications by combining a first resin (polymerized from a monomer mixture including styrene, divinylbenzene, and ethylene) with a second resin (including a bismaleimide-modified polyphenylene ether resin). Furthermore, by introducing a crosslinker including divinylbenzene, the low dielectric constant electrical specifications can be maintained while at the same time increasing the glass transition temperature and improving the flowability, thereby improving the overall processability. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0018] Hereinafter, embodiments of the present invention will be described in detail. However, these embodiments are merely examples, and the disclosure of the present invention is not limited thereto.

[0019] Here, the ranges indicated in this specification as "a value to another value" are general expressions to avoid listing all values ​​within the range. Thus, the description of a particular numerical range encompasses any numerical value within this numerical range and any smaller numerical range bounded by any numerical value within that numerical range, as if such any numerical value and such smaller numerical range were expressly set forth in the specification.

[0020] The resin composition of the present invention includes a resin base material, a non-halogen flame retardant, spherical silica, and a siloxane coupling agent. Specifically, the resin base material includes a first resin, a second resin, and a crosslinking agent. The first resin is polymerized with a monomer mixture including styrene, divinylbenzene, and ethylene. Furthermore, the second resin includes a bismaleimide-modified polyphenylene ether resin. The crosslinking agent is divinylbenzene. Each of the above components will be described in detail below.

[0021] Resin Substrate

[0022] In the present invention, the resin substrate refers to a resin component in the resin composition, and includes the first resin, the second resin, the SBS resin, and a crosslinking agent between the polymer resins. Each of the above components will be described below.

[0023] [First resin]

[0024] In this embodiment, the first resin is polymerized by a first monomer mixture containing styrene, divinylbenzene, and ethylene. In the first monomer mixture, the molar ratio of styrene:divinylbenzene:ethylene is 1:1:1 to 2:2:1. That is, the first resin has a styrene group ratio of 10% to 40%, a divinylbenzene group ratio of 10% to 40%, and a vinyl group ratio of 10% to 20%. In some embodiments, the number average molecular weight (Mn) of the first resin may be about 4500 to 6500. In some embodiments, the content of the first resin is, for example, 30 parts by weight to 60 parts by weight, preferably, for example, 35 parts by weight to 45 parts by weight, relative to 100 parts by weight of the resin base. When the first resin is added to the resin composition, the dielectric constant (Dk) and dielectric loss tangent (Df) of the resin composition can be effectively reduced to achieve electrical specifications with a low dielectric constant.

[0025] [Second resin]

[0026] In this embodiment, the second resin may include a bismaleimide (BMI) modified polyphenylene ether (PPE) resin. For example, the second resin of the present invention may be a bismaleimide modified polyphenylene ether resin (PPE-BMI) disclosed in Taiwan Patent Publication No. 1774559. The disclosure of Taiwan Patent Publication No. 1774559 is incorporated herein by reference in its entirety.

[0027] For example, the chemical structure of a bismaleimide-modified polyphenylene ether resin can be represented by the following chemical formula: [ka] wherein R is, for example, a direct bond, methylene, ethylene, isopropylene, 1-methylpropylene, pyrenylene, or fluorenylene; n is an integer of 3 to 25, and preferably an integer of 10 to 18.

[0028] The bismaleimide-modified polyphenylene ether resin may be prepared by the preparation method disclosed in Taiwan Patent Publication No. 1774559, but the present invention is not limited thereto. The bismaleimide-modified polyphenylene ether resin may be prepared by, for example, other suitable modification methods.

[0029] In some embodiments, the content of the second resin is, for example, 20 parts by weight to 40 parts by weight, preferably, for example, 30 parts by weight to 40 parts by weight, relative to 100 parts by weight of the resin substrate, but is not limited thereto. The chemical structure of the second resin has a main chain of polyphenylene ether, and the terminal is modified with a highly heat-resistant reactive group (i.e., bismaleimide), so that the second resin has a relatively low dielectric constant and a relatively low dielectric loss tangent.

[0030] [SBS resin]

[0031] In the present embodiment, the SBS resin refers to a styrene-butadiene-styrene block copolymer (SBS). The SBS resin may be polymerized with a second monomer mixture containing styrene, 1,2-butadiene, and 1,4-butadiene. In the second monomer mixture, the molar ratio of styrene:1,2-butadiene:1,4-butadiene may be 1:6:1 to 4:9:3. That is, the SBS resin has a styrene group ratio of 10% to 40%, a 1,2-butadiene group ratio of 60% to 90%, and a 1,4-butadiene group ratio of 10% to 30%. The SBS resin has a weight average molecular weight (Mw) of about 3500 to 5500. In some embodiments, the content of the SBS resin is, for example, 0 parts by weight to 30 parts by weight with respect to 100 parts by weight of the resin substrate, but is not limited thereto. The addition of SBS resin to the resin composition reduces phase separation between the resins and improves flow and filling properties, thereby improving overall processability while maintaining low dielectric constant properties.

[0032] [Crosslinking agent]

[0033] The crosslinking agent is used to increase the crosslinking degree of the thermosetting resin, adjust the rigidity and toughness of the substrate, and adjust the processability. Common crosslinking agents are, for example, 1,3,5-triallyl cyanurate (TAC), triallyl isocyanurate (TAIC), trimethallyl isocyanurate (TMAIC), diallyl phthalate, divinylbenzene, or a combination of one or more of 1,2,4-triallyl trimellitate. In the present invention, the crosslinking agent includes at least a divinylbenzene (DVB)-based crosslinking agent. In some embodiments, the content of the divinylbenzene crosslinking agent is, for example, 10 parts by weight to 40 parts by weight, preferably, for example, 10 parts by weight to 30 parts by weight, based on 100 parts by weight of the resin base. The incorporation of a vinylbenzene crosslinker into the resin composition allows the electrical specifications of low dielectric constant to be maintained while at the same time increasing the glass transition temperature and improving the flow properties of the resin, thereby improving overall processability.

[0034] Halogen-free flame retardants

[0035] In the present embodiment, specific examples of the non-halogen flame retardant include phosphate esters selected from triphenyl phosphate (TPP), resorcinol diphosphate (RDP), bisphenol A bis(diphenyl)phosphate (BPAPP), bisphenol A bis(dimethyl)phosphate (BBC), resorcinol diphosphate (CR-733S), resorcinol-bis(di-2,6-dimethylphenylphosphate) (PX-200), and the like, or polydi(phenoxy)phosphazene (SPB-100), ammonium polyphosphate, melamine polyphosphate (MPP, i.e., Melamine Polyphosphate), melamine cyanurate (Melamine Polyphosphate), and the like. or a combination of one or more selected from DOPO flame retardants such as DOPO (e.g., structural formula C), DOPO-HQ (e.g., structural formula D), bisDOPO-derived structures (e.g., structural formula E), and phosphorus-based flame retardants selected from aluminum-containing hypophosphite lipids (e.g., structural formula F). In some embodiments, the amount of halogen-free flame retardant is, for example, 20 phr to 50 phr based on 100 parts by weight of the resin base. [ka]

[0036] Spherical Silica

[0037] In this embodiment, the spherical silica is preferably prepared by a synthetic method in order to reduce electrical properties and maintain fluidity and packing properties. The spherical silica is surface-modified with acrylic or vinyl, has a purity of 99.0% or more, and has an average particle size (D50) of about 2.0 μm to 3.0 μm. In some embodiments, the amount of spherical silica added is, for example, 20 parts by weight to 50 parts by weight based on 100 parts by weight of the total weight of the resin base and the non-halogen flame retardant.

[0038] Siloxane Coupling Agent

[0039] In this embodiment, the siloxane coupling agent includes, but is not limited to, siloxane. In addition, depending on the type of functional group, it can be divided into aminosilane compounds (aminosilanes), epoxysilane compounds (epoxide silanes), vinylsilane compounds, estersilane compounds, hydroxysilane compounds, isocyanate silane compounds, methacryloxysilane compounds, and acryloxysilane compounds. In some embodiments, the amount of the siloxane coupling agent added is, for example, 0.1 phr to 5 phr with respect to 100 parts by weight of the resin composition. By adding a siloxane coupling agent to the resin composition, the compatibility with glass fiber cloth or powder and the degree of crosslinking are improved.

[0040] Additives

[0041] The resin composition of the present invention may contain other additives such as a peroxide initiator in addition to the above components.

[0042] It should be noted that the resin composition of the present invention can be processed into prepregs and / or copper-clad laminates (CCLs) according to actual design requirements. Therefore, the prepregs and copper-clad laminates manufactured using the resin composition of the present invention also have better reliability (they can maintain the desired electrical properties). In some preferred embodiments, the dielectric constant of the substrate (or prepreg) made with the resin composition is about 3.0-3.1, the dielectric loss tangent is less than about 0.0015, and thus achieves the electrical specification of ultra-low dielectric constant, and the glass transition temperature can be even higher, such as above 210°C.

[0043] The resin composition of the present invention will be described in detail below with reference to examples, although the present invention is not limited to these examples.

[0044] Working Example

[0045] In order to prove that the resin composition proposed by the present invention can maintain a low dielectric constant and / or a low dielectric tangent while improving the fluidity and glass transition temperature of the resin composition, and can achieve electrical specifications of a low dielectric constant, the present invention will be specifically described below with reference to examples.

[0046] Preparation of the second resin

[0047] A low molecular weight polyphenylene ether resin material having a number average molecular weight (Mn) of 12,000 or less, or 10,000 or less (for example, Mn=500, 1400, 1600, or 1800) was dissolved in dimethylacetamide, and then potassium carbonate and tetrafluoronitrobenzene were added. The reaction solution was heated to 140°C and reacted for 8 hours, then cooled to room temperature and filtered to remove solids. The filtrate was precipitated with methanol / water, and the precipitate was used as a nitrated polyphenylene ether resin. Next, the nitrated polyphenylene ether resin was dissolved in dimethylacetamide and hydrogenated at 90°C for 8 hours to obtain an aminated polyphenylene ether resin. Next, the aminated polyphenylene ether resin was put into toluene, maleic anhydride and p-toluenesulfonic acid were added, and the mixture was heated to 120°C and refluxed, and reacted for 8 hours to prepare a second resin. The second resin was a bismaleimide-modified polyphenylene ether resin (PPE-BMI).

[0048] Preparation of resin composition

[0049] The resin composition shown in Table 1 was mixed with toluene to form a varnish of a thermosetting resin composition, and the varnish was impregnated into Nanya glass fiber cloth (manufactured by Nanya Plastics, cloth type 1078LD) at room temperature, and then dried at 170°C for several minutes (impregnator) to obtain a prepreg with a resin content of 79% by weight. Finally, four prepregs were laminated in layers between two sheets of copper foil with a thickness of 35 microns. A pressure of 25 kg / cm was applied. 2 After holding the temperature at 85°C for 20 minutes, the temperature was increased to 210°C at a rate of 3°C / min and then held at that temperature for 120 minutes.Then, the temperature was gradually cooled to 130°C to obtain a copper-clad laminate with a thickness of 0.59 mm, and various characteristics were evaluated.

[0050] Evaluation method

[0051] The copper-clad laminates produced in each of the Examples and Comparative Examples were evaluated by the following methods, and the results are shown in Table 1.

[0052] Glass transition temperature (° C.): Tested with a dynamic mechanical analyzer (DMA).

[0053] Water absorption rate (%): The sample was heated in a pressure cooker at 120°C and 2 atm for 120 minutes, and the change in weight before and after heating was calculated.

[0054] Solder heat resistance at 288°C (seconds): The sample was heated in a pressure cooker at 120°C and 2 atmospheres for 120 minutes, then immersed in a soldering furnace at 288°C. The time required for the sample to explode and peel off was recorded.

[0055] Dielectric constant Dk: The dielectric constant Dk at a frequency of 10 GHz was tested using a dielectric constant analyzer HP Agilent E4991A.

[0056] Dielectric loss tangent Df: The dielectric loss Df at a frequency of 10 GHz was tested using a dielectric constant analyzer HP Agilent E4991.

[0057] Resin flow rate: Pressed at 200±25 PSI for 10 minutes using a press at 170°C±2.8°C. After melting and cooling, a disk was punched out. The disk was accurately weighed and the resin flow rate was calculated.

[0058] Resin phase separation (slice analysis): Step 1: Copper clad laminate was cut to a size of 1 cm x 1 cm and placed in a mold for resin grouting. Step 2: After the resin was completely dried and cured, the samples were ground and polished. Step 3: The samples were analyzed using a high resolution microscope such as OM / SEM to see if there was any resin phase separation within the sample.

[0059] In Table 1, the details of each component are as follows. First resin: LDM-03 (purchased from Denka Co., Ltd.) Second resin: Use the prepared second resin SBS resin: 1,2-SBS Type-C (purchased from Nippon Soda Co., Ltd.) Crosslinker DVB: Divinylbenzene crosslinker Crosslinker TAIC: Triallyl isocyanuric acid crosslinker Non-halogen flame retardant: PQ-60 (purchased from Chin Yee Chemical Company) Silicon dioxide: EQ2410-SMC (purchased from Third Age Technology Company) Peroxide: Luperox F (purchased from Arkema Co., Ltd.) Siloxane coupling agent: Z-6030 (purchased from Dow Corning Co., Ltd.)

[0060] Table 1: Compositions and physical properties of the resin compositions of Comparative Examples 1 to 3 and Examples 1 to 3

[0061] [Table 1] JPEG2024180228000004.jpg179164

[0062] In Table 1, Comparative Examples 1 to 3 used triallylisocyanuric acid (TAIC) as the crosslinking agent, and Examples 1 to 3 used divinylbenzene (DVB) as the crosslinking agent. As a result, compared to Comparative Examples 1 to 3 using the TAIC crosslinking agent, Examples 1 to 3 using the DVB crosslinking agent (comparison between Example 1 and Comparative Example 1, comparison between Example 2 and Comparative Example 2, comparison between Example 3 and Comparative Example 3), while maintaining the same electrical specifications of low dielectric constant, showed an increase in glass transition temperature, improved resin fluidity, and reduced dielectric loss tangent (Df).

[0063] From the above, in the resin composition of the present invention, a first resin (polymerized from a monomer mixture containing styrene, divinylbenzene, and ethylene) and a second resin (containing a bismaleimide-modified polyphenylene ether resin) are blended. As a result, the resin composition of the present application can have low dielectric constant electrical specifications (low dielectric constant, low dielectric tangent, etc.), and by introducing a crosslinking agent containing divinylbenzene, the effect of increasing the glass transition temperature and improving fluidity while maintaining the electrical properties of the substrate is obtained, thereby improving the overall processability.

[0064] Although the present invention has been described with reference to the above embodiments, it will be apparent to those skilled in the art that modifications can be made to the described embodiments without departing from the spirit of the invention. Accordingly, the scope of the present invention is defined by the appended claims rather than the above detailed description. [Industrial Applicability]

[0065] The resin composition of the present invention can be applied to resins in any form.

Claims

1. a resin substrate including a first resin polymerized from a first monomer mixture including styrene, divinylbenzene, and ethylene, a second resin including a bismaleimide-modified polyphenylene ether resin, and a divinylbenzene-based crosslinking agent; Halogen-free flame retardants, Spherical silica; A resin composition comprising:

2. The resin composition according to claim 1, wherein the content of the first resin is 30 parts by weight to 60 parts by weight, the content of the second resin is 20 parts by weight to 40 parts by weight, and the content of the divinylbenzene-based crosslinking agent is 10 parts by weight to 30 parts by weight, relative to 100 parts by weight of the resin base material.

3. The resin composition according to claim 1, wherein the amount of the non-halogen flame retardant added is 20 phr to 50 phr based on 100 parts by weight of the resin base material.

4. 2. The resin composition according to claim 1, wherein the amount of the spherical silica added is 20 parts by weight to 50 parts by weight per 100 parts by weight of the total of the resin base material and the non-halogen flame retardant.

5. 2. The resin composition according to claim 1, wherein the molar ratio of styrene:divinylbenzene:ethylene in the first monomer mixture is from 1:1:1 to 2:2:

1.

6. The resin composition according to claim 1, wherein the first resin has a number average molecular weight of 4,500 to 6,500.

7. 10. The resin composition of claim 1, wherein the resin base further comprises an SBS resin polymerized from a second monomer mixture comprising styrene, 1,2-butadiene, and 1,4-butadiene.

8. The resin composition according to claim 7, wherein the molar ratio of styrene:1,2-butadiene:1,4-butadiene in the second monomer mixture is from 1:6:4 to 4:9:

3.

9. The resin composition according to claim 7, wherein the content of the SBS resin is 0 to 30 parts by weight based on 100 parts by weight of the resin substrate.

10. The resin composition according to claim 7, wherein the weight average molecular weight of the SBS resin is 3,500 to 5,500.

11. The resin composition according to claim 1, wherein the spherical silica is surface-modified with acrylic or vinyl and has an average particle size of 2.0 μm to 3.0 μm.

12. The electrical specification of the resin composition is a dielectric constant of 3.0 to 3.1 and a dielectric loss tangent of less than 0.0015, and the heat resistance specification of the resin composition is a glass transition temperature of more than 210 ° C. The resin composition according to claim 1.

Citation Information

Patent Citations

  • Polyphenylene ether resin modified with bismaleimide, method for producing the same, and substrate material for circuit board

    US20230091594A1

  • Curable composition and cured article thereof

    WO2021112088A1

Cited By

  • Resin composition, and prepreg, resin-coated film, resin-coated metal foil, metal-clad laminate, and wiring board each obtained using same

    WO2025142541A1

  • Curable resin composition and cured product thereof

    WO2026177077A1

  • Composition and cured body

    WO2026205146A1